2018
DOI: 10.1002/aoc.4374
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of transition metal complexes with a tridentate NNO amoxicillin derived Schiff base. Synthesis and characterization

Abstract: From the reaction of amoxicillin (1) antibiotic with 2,6−diaminopyridine (2) an amoxicillin−based Schiff base (HL) (3) was obtained and its transition metal Schiff base complexes were synthesized. Spectroscopic and physicochemical techniques, namely, UV−Vis, FT−IR, 1H−NMR, EPR, mass spectrometry, molar conductance, magnetic susceptibility, molecular modelling, together with elemental and thermal analyses, were used to characterize the synthesized compounds. Spectral and magnetic data suggested an octahedral ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The evolutionary mechanism of bacterial resistance needs to be controlled or reduced by search for sustainable alternative in the field of biomedicine and biotechnology (Anacona, Mago, & Camus, 2018; Karthik, Dhanuskodi, et al, 2018b; Savale, Ghotekar, Pansambal, & Pardeshi, 2017). These new techniques would enhance production capacity for synthesis of new antimicrobial agents from small experimanetal scales to large industrial scales by using advance technology.…”
Section: Introductionmentioning
confidence: 99%
“…The evolutionary mechanism of bacterial resistance needs to be controlled or reduced by search for sustainable alternative in the field of biomedicine and biotechnology (Anacona, Mago, & Camus, 2018; Karthik, Dhanuskodi, et al, 2018b; Savale, Ghotekar, Pansambal, & Pardeshi, 2017). These new techniques would enhance production capacity for synthesis of new antimicrobial agents from small experimanetal scales to large industrial scales by using advance technology.…”
Section: Introductionmentioning
confidence: 99%
“…When we compare these findings with antibacterial activity of complex 1 [27], it can be concluded that the ligand abb and especially its nickel complex have much better activities against S. aureus and comparable antibacterial activity on E. coli. One should expect higher antibacterial activity in compounds containing sulfur in the structure, but conformation, i.e., planarity vs. nonplanarity of ligands and possible π-π interactions play a very important role in binding to active sites [33,34].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of synthesized thiosemicarbazone ligands and copper(II) complexes (5 and 50 μg/ml) was investigated by agar disc diffusion [9,10] against Bacillus thuringiensis (Gram-positive) and Escherichia coli (Gram-negative) and reported in terms of mm. However, the test was performed in the agar medium with the positive (chloramphenicol) and negative controls (DMF).…”
Section: Antibacterial Screeningmentioning
confidence: 99%